2007
DOI: 10.1007/s11199-007-9368-0
|View full text |Cite
|
Sign up to set email alerts
|

How Lesbian and Heterosexual Parents Convey Attitudes about Gender to their Children: The Role of Gendered Environments

Abstract: We studied associations among parents' gender role attitudes, gender stereotyping in children's environments, and children's gender role attitudes and whether these associations were similar for families with lesbian and heterosexual parents. Fifty-seven 4-to 6-year-olds and 114 parents from the US participated. Parents completed selfreport questionnaires and responded to interview questions. Researchers collected data regarding the child's environment and attitudes about gender. Results revealed that children… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
70
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(71 citation statements)
references
References 38 publications
1
70
0
Order By: Relevance
“…Research has found that when parents have more traditional views regarding gender roles, their children also tend to think in more traditional terms (Epstein & Ward, 2011; Fulcher, 2010; Sutfin, Fulcher, Bowles, & Patterson, 2008); on the other hand, when parents hold more egalitarian values, their children tend to have less traditional gender-role attitudes (Sutfin et al, 2008). Fathers’ ideology has typically been overlooked in this literature.…”
Section: Introductionmentioning
confidence: 99%
“…Research has found that when parents have more traditional views regarding gender roles, their children also tend to think in more traditional terms (Epstein & Ward, 2011; Fulcher, 2010; Sutfin, Fulcher, Bowles, & Patterson, 2008); on the other hand, when parents hold more egalitarian values, their children tend to have less traditional gender-role attitudes (Sutfin et al, 2008). Fathers’ ideology has typically been overlooked in this literature.…”
Section: Introductionmentioning
confidence: 99%
“…Most studies (the Hoeffer 375 and Kirkpatrick studies from 1981, 376 the Golombok study from 1983, 377 the Brewaeys study from 1997, 378 the MacCallum and Golombok study from 2004, 379 and the Farr study from 2010 380 ) found no significant differences in gender-related matters. 381 Another study (Suftin, 2008) 382 did find some differences in the gender attitudes of the children of lesbian mothers when compared to those of children of heterosexual parents, with the 370 Id. The difference was greater between the boys and girls of heterosexual parents and those of lesbian mothers than it was between the former and the boys and girls of gay fathers.…”
Section: B Assessing the Empirical Literature From The Rational Basimentioning
confidence: 98%
“…347 In another article published in 2008, Erin Suftin and her team of researchers studied gender-related issues by comparing twenty-nine families headed by lesbian couples with twenty-eight families headed by heterosexual ones. 348 The study included fifty-seven four-to-six-year-old children. 349 Relying on questionnaires, the researchers found that the lesbian mothers had "more liberal [gender] attitudes than did heterosexual parents."…”
mentioning
confidence: 99%
“…As children interact with their environment they develop a sense of value for the tasks they perform (Bussey & Bandura, 1999), such as playing with gendered toys (Pomerleau et al, 1990) or decorating a bedroom with gender-specific artifacts Sutfin et al, 2008). Pomerleau et al (1990) and Rheingold and Cook (1975) investigated children"s bedrooms and found that boys" bedrooms contained more varieties of toys, more sports equipment and machines, and more animal décor items than girls" bedrooms, while girls" bedrooms contained more dolls and domestic toys.…”
Section: Symbolic Interactionism: Spaces Objects Gender Identitiesmentioning
confidence: 99%